Sufi Epistemology: being the earliest exposition in Kitâb al-Luma’ of al-Sarrâj and its manifestation in the works of Indonesian Sufis - Ihsan, Nur Hadi Ihsan; Mohd Amin, Wan Mohd Azam; Arroisi, Jarman; Mudin, Moh. Isom (Universitas Darussalam, Gontor, Indonesia, 2021)
Kitâb al-Luma’ fî al-Tas}awwuf of al-Sarrâj (d. 378H./988CE.) is the earliest work in Sufism survived and arrived at us. It did not only record the history of Sufism up to that time but also promoted and placed its position among other disciplines in the history of intellectual and spiritual traditions of Islam. With this work, al-Sarrâj formulated Sufi epistemology in its earliest development. This paper attempts to explore the Sufi epistemology of al-Sarrâj, which will cover the discussion about his classification and hierarchy of knowledge, his analysis of the position of Sufism among other knowledge, and then his elaboration of the methodology of Sufism. Before ending the discussion, the paper will read the works of Indonesian Sufis using Sufi epistemology as a perspective. This study finds that al-Sarrâj was successfully constructed Sufi epistemology in its initial emergence. He placed Sufism as a discipline of knowledge and posed it at the highest level in the structural hierarchy of knowledge. Indonesian Sufis from Sufi epistemology, it appears that in the early days of their birth, these works were colored by the epistemology of philosophical Sufism. It was only later that the epistemology of Sunni Sufism came into existence, and this became more evident in the following periods in the development of Sufism in this country.